2020
DOI: 10.1097/ta.0000000000002976
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of preinjury anticoagulation in patients with traumatic brain injury: A systematic review and meta-analysis

Abstract: BACKGROUND Traumatic brain injury (TBI) is a leading cause of injury-related deaths and neurological disability globally. Considering the widespread anticoagulant use among the aging population, we aimed to perform a systematic review and meta-analysis to evaluate the prognostic significance of preinjury anticoagulation in TBI patients. METHODS This systematic review was conducted according to a predefined protocol (International Prospective Register of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 65 publications
0
21
0
1
Order By: Relevance
“…1-3,7 Pre-injury anticoagulant use also has been shown to increase the severity of head injury and risk of mortality. 2,4-6 The current study, and existing studies, show an increased mortality in older, anticoagulated patients, which raises the question as to whether these criteria should be added as a TTA criteria. Callahan et al 10 examined the impact of using age of 65 years or older on antithrombotic medication as a criterion for TTA.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…1-3,7 Pre-injury anticoagulant use also has been shown to increase the severity of head injury and risk of mortality. 2,4-6 The current study, and existing studies, show an increased mortality in older, anticoagulated patients, which raises the question as to whether these criteria should be added as a TTA criteria. Callahan et al 10 examined the impact of using age of 65 years or older on antithrombotic medication as a criterion for TTA.…”
Section: Discussionmentioning
confidence: 66%
“…8 Pre-injury anticoagulant use has been associated with a 2.39 times increase in overall mortality in TBI patients. 6 An Eastern Association for the Surgery of Trauma (EAST) practice management guideline acknowledges this risk and urges for an expedited assessment and treatment in patients that are older and taking anticoagulant or antiplatelet agents, as these increase the risk of hemorrhage after an injury. 9 Anticoagulated patients with suspected TBI were previously triaged as a second tier trauma team activation (TTA) at the study institution.…”
Section: Introductionmentioning
confidence: 99%
“…Like antiplatelet drugs, many patients who suffer TBI are now on anticoagulants, with an increasing proportion on direct oral anticoagulants (DOAC) rather than vitamin K antagonists such as warfarin. One systematic review showed that pre‐injury anticoagulation was associated with an increased mortality risk (OR 2.39 (95%CI 1.63–3.50); p < 0.00001); however, only a small minority of patients were taking a DOAC (5%) with the remainder taking vitamin K antagonists [27]. A small cohort study focusing on patients with minor head injury taking a DOAC showed an increase in the incidence of adverse outcomes, defined as a composite of requirement for neurosurgery, intracranial haemorrhage or death (3.4% (95%CI 1.4–8.0%)) [28], compared with patients who were not anticoagulated.…”
Section: Transfusion and Coagulationmentioning
confidence: 99%
“…Traumatic brain injury (TBI) is often described as an insult due to a bump, blow or jolt to the head which leads to impairment of brain function (1). The spectrum of TBI can range from mild alteration in consciousness to a severe comatose state or death with or without evidence of intracranial hemorrhage (ICH) (2).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of patients sustaining TBI, research suggests that preinjury use of anticoagulants (12) is a significant risk factor for developing ICH after TBI whereas corresponding evidence for antiplatelet drugs is ambiguous (13,14). Recent meta-analysis studies have assessed the impact of preinjury anticoagulation on outcomes of general trauma and TBI patients and have noted significantly increased mortality in anticoagulant users as compared to controls (1,10). However, similar evidence for antiplatelet drugs is scarce.…”
Section: Introductionmentioning
confidence: 99%